Adaptations of Calvinism in Reformation Europe: essays in honour of Brian G. Armstrong - Holt, Mack P. ca. 20./21. Jh.; Armstrong, Brian G. (St. Andrews studies in Reformation history, 2007)
Introduction -- Calvin, Beza, and Geneva -- John Calvin's interpretation of Psalm 22 / Bernard Roussel -- Was Calvin a crypto-zwinglian? / Anthony N.S. Lane -- Development and coherence in Calvin's institutes : the case of baptism / David F. Wright -- God's eternal decree and its temporal execution : the role of this distinction in Theodore Beza's theology / Donald Sinnema -- Reformed ideas outside Geneva -- A lay voice in sixteenth-century ecumenics : Katharina Schütz Zell in dialogue with Johannes Brenz, Conrad Pellican, and Caspar Schwenckfeld / Elsie Anne McKee -- Vera ecclesiae concordia : Martin Bucer's blueprint for the Reformation in France / Willem van Spijker -- Politique and spiritualist tolerance : Bodin's heptaplomeres and Coornhert's synodus / Pieter G. Voogt -- The Reformation in France -- The Genevan model and Gallican originality in the french reformed tradition / Raymond A. Mentzer -- Divisions within French calvinism : Philippe Duplessis-Mornay and the Eucharist / Mack P. Holt -- The Jacques Royer affair, 1604-1624 : an argument over liturgy in Geneva and France / Robert M. Kingdon -- The reformations in England and Scotland -- A calvinist bishop at the court of King Charles I / Daniel Steere -- Popular piety : the imposition of Elizabethan church discipline in the Deanery of Stottesden / Brett Armstrong -- Marginal at best : John Knox's contribution to the Geneva Bible / Dale W. Johnson